1998
DOI: 10.1111/0022-1082.244195
|View full text |Cite
|
Sign up to set email alerts
|

Block Share Purchases and Corporate Performance

Abstract: This paper investigates the causes and consequences of activist block share purchases in the 1980s. We find that activist investors were most likely to purchase large blocks of shares in highly diversified firms with poor profitability. Activists were not less likely to purchase blocks in firms with shark repellents and employee stock ownership plans. Activist block purchases were followed by increases in asset divestitures, decreases in mergers and acquisitions, and abnormal share price appreciation. Industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
272
9
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(312 citation statements)
references
References 50 publications
28
272
9
3
Order By: Relevance
“…For example, Bethel, Liebeskind, and Opler (1998) find that company performance improves after an activist investor purchases a block of shares. In addition, Kang and Shivdasani (1995), and Kaplan and Minton (1994) have found that the presence of large shareholders in a firm is associated with management turnover, suggesting that these shareholders provide a monitoring function.…”
mentioning
confidence: 99%
“…For example, Bethel, Liebeskind, and Opler (1998) find that company performance improves after an activist investor purchases a block of shares. In addition, Kang and Shivdasani (1995), and Kaplan and Minton (1994) have found that the presence of large shareholders in a firm is associated with management turnover, suggesting that these shareholders provide a monitoring function.…”
mentioning
confidence: 99%
“…2 Unlike Bethel, Liebeskind and Opler (1998), they find that firms with private equity placements have relatively high market-to-book ratios, as well as high capital expenditures prior to the private placement.…”
Section: Introductionmentioning
confidence: 73%
“…As a comparison, we also perform the same set of analyses on 2 A "private equity placement" describes a company's cash sale of its securities made in reliance upon exemptions from registration requirements contained in the applicable securities legislation. Private placement investments often are limited to institutional investors, accredited/sophisticated investors, hedge funds, venture capitalists, and corporate insiders.…”
Section: Introductionmentioning
confidence: 99%
“…Shareholder activism can take many forms. These include binding and non-binding (or precatory) shareholder proposals, quiet negotiations to obtain governance or other changes, and campaigns to withhold votes or vote against directors (Kahan and Rock, 2006;Bethel et al, 1998;Becht et al, 2006;O'Rourke, 2003;Rehbein, Waddock and Graves, 2004). One of the most popular tools of shareholder activists are proxy fights.…”
Section: Causes and Forms Of Shareholder Activismmentioning
confidence: 99%
“…In the finance and management literature, the pursuit of shareholder value is assumed to be the main driver of shareholder activism (Del Guercio and Hawkins, 1999;Ryan and Schneider, 2002;Bethel et al, 1998;Becht et al, 2006;Brav et al, 2008). In their 1996 study, Karpoff, Malatesta and Walkling identified three primary categories of issues that were the subjects of shareholder proposals:…”
Section: Causes and Forms Of Shareholder Activismmentioning
confidence: 99%